PENGEMBANGAN E-MODUL PENDIDIKAN PANCASILA MENGINTEGRASIKAN PROFIL PELAJAR PANCASILA KELAS IV SEKOLAH DASAR - M.Pd, Yulianti; Ngui, Heni Hardianti; Ladamay, Iskandar (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2023)
The purpose of this study was to determine the feasibility and practicality of the Pancasila Education E-Module on constitutional material and norms in class IV elementary school society by integrating Pancasila student profiles. The development research model used is the ADDIE model which consists of five stages, namely: Analysis, Development, Design, Implementation, and Evaluation. The subjects of this research were class IV students at SD Negeri Sukun 3 Malang. The instruments used were material expert validation sheets, media expert validation sheets, linguist validation sheets to test the e-module validity, and teacher and student response sheets for practicality tests. The results of the study obtained the validation results of material experts with a percentage of 82.69% who had very valid criteria, media experts with a percentage of 86.36% who had very valid criteria, and linguists with a percentage of 83.33% who had very valid criteria. For the teacher's response questionnaire, it obtained a percentage of 81.66% with very practical criteria, the average student response questionnaire obtained a percentage of 87.82% with very practical criteria. Based on these results, e-modules can be used in learning activities because they meet the criteria of being very valid and very practical.